THE ANALYSIS OF CHINA'S AGRARIAN REFORM POLICY - Sharipkazy, Н.; Nurzhayeva, А. М. (Journal of Oriental Studies, 2024)
China is a large agricultural country since ancient times. In China, priority has always been given to agricultural economic policy. Because China's social development is directly related to agriculture. The article provides an in-depth study of the agricultural policy of the People's Republic of China from its establishment to the present and gives a historical assessment. The agrarian reform carried out in China after the 1950s, based on the economic concept of the plan, formed a three-level production structure: Xiaodui (small production unit), Dadui (large production unit) and Renmin Gongshe (People's Commune). However, social practice has proven the fallacy of this system through bitter examples. The purpose of the article is to analyze and study China's reforms and policies in the field of agriculture. This study is valuable not only in the theoretical aspect, which allows us to assess the evolutionary development of China in the agricultural sector, but also has great practical significance in the experience of changing the traditional agricultural sector of China. The scientific value of our article is important, since the topic has not been previously studied by domestic researchers. To study the issues raised in the article, classical and modern methods of the humanities were used. Using the methodology of political science, the features of the policy pursued in each historical period were described; the methods of constructivism were used in the study. We also tried to deeply reveal the scientific content of our article, using the methods of analysis, synthesis, induction and deduction in the methods of scientific research that are widely used in modern times. Previously, China imported agricultural products from foreign countries, including America. However, recent changes in world geopolitics, the escalation of the trade war between the United States and China will force China to import grain products from other countries. Judging by this situation, China has the right to show interest in importing agricultural products from neighboring Kazakhstan. Based on this, it can be assumed that cooperation and trade relations between Kazakhstan and China in the agricultural sector will continue to revive and develop. Key words: Chinese agricultural policy, process of agrarian reform, transformation of the agricultural production system, export-import, problems.